Interpretation of leisure sports in the pandemic situation of COVID 19 - Ling, P. (World Leisure Journal, 2020)
There was a phenomenon that is gratifying: during the pandemic of COVID 19, home leisure sports products were selling well. The stduy found that: during the pandemic, people paid more attention to leisure sports, and leisure sports became one of the most important lifestyles of ordinary people and it reminded the fitness value, entertainment value as well as social interaction value in the lives of people. It is the healthiest lifestyle during the pandemic of COVID 19.